2022
DOI: 10.1186/s12931-022-02135-1
|View full text |Cite
|
Sign up to set email alerts
|

Upregulating carnitine palmitoyltransferase 1 attenuates hyperoxia-induced endothelial cell dysfunction and persistent lung injury

Abstract: Background Bronchopulmonary dysplasia (BPD) is a chronic lung disease in premature infants that may cause long-term lung dysfunction. Accumulating evidence supports the vascular hypothesis of BPD, in which lung endothelial cell dysfunction drives this disease. We recently reported that endothelial carnitine palmitoyltransferase 1a (Cpt1a) is reduced by hyperoxia, and that endothelial cell-specific Cpt1a knockout mice are more susceptible to developing hyperoxia-induced injury than wild type mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…To determine the role of Areg signaling in the developing lung ECs, we used the fetal murine lung endothelial cell line, MFLM-91U, because it has been widely used to study the effects of HO on the EC biology of developing murine lungs in a robust manner [60][61][62]. Consistent with our in vivo findings in whole lungs, HO increased Areg mRNA expression in the lung ECs.…”
Section: Discussionsupporting
confidence: 66%
“…To determine the role of Areg signaling in the developing lung ECs, we used the fetal murine lung endothelial cell line, MFLM-91U, because it has been widely used to study the effects of HO on the EC biology of developing murine lungs in a robust manner [60][61][62]. Consistent with our in vivo findings in whole lungs, HO increased Areg mRNA expression in the lung ECs.…”
Section: Discussionsupporting
confidence: 66%
“…Currently, the protective effect of up-regulating FAO expression and its key mediators on pulmonary endothelial cells has also been validated in an ALI murine model induced by hyperoxia [ 67 ]. Both L-carnitine and baicalin can mitigate the dysregulation of apoptosis, migration, and angiogenesis in pulmonary endothelial cells induced by hyperoxia through upregulation of CPT1A [ 68 ].…”
Section: The Impact Of Fatty Acid Oxidation On Alimentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org investigation demonstrated that baicalin can reduce lung mitochondrial lipid peroxidation and antioxidant activity induced by linoleic acid hydroperoxide (LHP) in vitro (Liau et al, 2019). Baicalin attenuated air embolism-induced acute lung injury (Li et al, 2009b) and severe burn-induced remote acute lung injury through the NLRP3 signaling pathway (Bai et al, 2018) and attenuated neonatal hyperoxia-induced endothelial cell dysfunction and alveolar and vascular simplification in adult mice by upregulating carnitine palmitoyltransferase 1a (Cpt1a) (Chang et al, 2022). These results suggest possible treatment approaches for employing baicalin to prevent persistent lung injury in some illnesses and injuries.…”
Section: Acute Lung Injury/acute Respiratory Distress Syndromementioning
confidence: 99%